2022
DOI: 10.1111/nep.14064
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among gut microbiota, hypoxia‐inducible factor and anaemia with chronic kidney disease

Abstract: Gut microbiota plays a vital role in human intestinal homeostasis, correlating strongly with the progression of numerous diseases. Recent researches provide powerful evidence that the connections exist between gut microbiota and renal anaemia. Gut microbiota may have an impact on renal anaemia by regulating the hypoxia-inducible factor (HIF) signalling, iron metabolism and inflammatory state. Because of this relationship, there may be potential treatments for renal anaemia. In this review, we will first provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Thus, changes in microbiota can result in abnormal colonocyte function [ 167 ]. In colonocytes, absorbed butyrate can be converted to acetyl-CoA through β-oxidation in mitochondria, contributing to the consumption of oxygen and activation of HIF-1α and transcription of its target genes [ 168 ]. Zhou et al [ 169 ] demonstrated that intestinal epithelial-specific deletion of HIF-1α changed the composition of the gut microbiota and decreased butyrate production, increasing the susceptibility of mice to induced colitis.…”
Section: The Gut-kidney Axis: a Role For Hypoxia-inducible Factor?mentioning
confidence: 99%
“…Thus, changes in microbiota can result in abnormal colonocyte function [ 167 ]. In colonocytes, absorbed butyrate can be converted to acetyl-CoA through β-oxidation in mitochondria, contributing to the consumption of oxygen and activation of HIF-1α and transcription of its target genes [ 168 ]. Zhou et al [ 169 ] demonstrated that intestinal epithelial-specific deletion of HIF-1α changed the composition of the gut microbiota and decreased butyrate production, increasing the susceptibility of mice to induced colitis.…”
Section: The Gut-kidney Axis: a Role For Hypoxia-inducible Factor?mentioning
confidence: 99%
“…[3][4][5]. The disrupted gut microbiota can increase the risk for several health complications, including decreased resistance against bacterial pathogens, predisposition to autoimmune and allergic diseases, and some chronic diseases [6][7][8]. Since VAs and PVAs are widely used in livestock and aquaculture around the world [9,10], exposure to them is unavoidable.…”
Section: Introductionmentioning
confidence: 99%